Analisis Teori Keagenan, Peran Tata Kelola, Dan Peran Tata Kelola Bisnis Untuk Mengatasi Konflik Kepentingan - Okta, Agatha Danar Kristia; Nursanita, Nursanita (Penerbit Goodwood, 2025)
Purpose: The aim of this study is to analyze the application of agency theory and the role of corporate and business governance in addressing conflicts of interest, using a case study of fraud committed by insurance agent Swita Glorite Supit from Sinarmas MSIG Life. Methodology: This study uses a descriptive qualitative approach. The research focuses on a real-life case involving Sinarmas MSIG Life, specifically examining governance practices and agent misconduct. No software was used, but the study is based on literature review, document analysis, and interpretation of agency theory principles in the context of a fraud case. Result: The findings reveal that information asymmetry and weak internal control systems are the root causes of agency-related issues. The analysis also highlights the importance of implementing good governance principles including transparency, accountability, and risk management to protect policyholders and uphold the reputation of the insurance industry Conclusions: The case of Swita Glorite Supit reflects a systemic failure in corporate and agency governance. The misconduct stems not only from individual actions but also from weak oversight, ineffective code of ethics implementation, and the lack of a strong ethical culture to prevent and detect fraud. Limitations: A limitation of the study is that it focuses on a single case and does not include quantitative data or perspectives from a broader range of agents or companies, which may affect generalizability. Contribution: This study contributes to the understanding of agency theory application in the financial services sector, particularly in insurance. It is useful for corporate governance practitioners, policymakers, insurance companies, and researchers in the fields of business ethics, governance, and risk management.